2020
DOI: 10.3390/antiox9040349
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe Prevents Ischemia/Reperfusion-Induced Oxidative Stress and Up-Regulates Nrf2/ARE and UPR Signaling Pathways

Abstract: Background: While reperfusion is crucial for survival after an episode of ischemia, it also causes oxidative stress. Nuclear factor-E2-related factor 2 (Nrf2) and unfolded protein response (UPR) are protective against oxidative stress and endoplasmic reticulum (ER) stress. Ezetimibe, a cholesterol absorption inhibitor, has been shown to activate the AMP-activated protein kinase (AMPK)/Nrf2 pathway. In this study we evaluated whether Ezetimibe affects oxidative stress and Nrf2 and UPR gene expression in cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Activation of AMPK was shown to inhibit ER stress in previous studies [19,20]. Ezetimibe, a cholesterol absorption inhibitor, was shown to reduce IR-induced oxidative stress and UPR pathway activation through activation of AMPK [22]. Pang et al proved that CAMKKβ/AMPK/mTOR-dependent signaling pathway was critical for inhibiting ER stress in cardiomyocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AMPK was shown to inhibit ER stress in previous studies [19,20]. Ezetimibe, a cholesterol absorption inhibitor, was shown to reduce IR-induced oxidative stress and UPR pathway activation through activation of AMPK [22]. Pang et al proved that CAMKKβ/AMPK/mTOR-dependent signaling pathway was critical for inhibiting ER stress in cardiomyocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthily, ERN-1 is an NF-κB activator that provides connections between ER stress, oxidative stress, and inflammatory processes between the cell death process [59]. It has been reported that oxidative and ER stress interplay through Nrf2 activation is crucial for cellular events, such as apoptosis and cell survival [60]. Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…Human cardiomyocyte ventricular primary cells (Celprogen, Torrance, CA, USA) were cultured following the recommended manufacturer’s protocols in extracellular matrix pre-coated flasks and/or well plates with a ready-to-use complete growth medium (Celprogen, Torrance, CA, USA), as previously described [ 37 ]. The choice of such cell lines was guided by previous evidence of their high reliability in evaluating oxidative stress and antioxidant signaling pathways [ 38 , 39 ] .…”
Section: Methodsmentioning
confidence: 99%
“…To induce different degrees of oxidative stress, THP-1 cells were incubated with increasing concentrations (20–100 μM) of tert-butyl hydroperoxide (TBHP) for 45 min at 37 °C. Intracellular ROS formation was determined using the CellROX Deep Red Flow Cytometry Assay Kit (Molecular Probe, Life Technologies, Carlsbad, CA, USA), as previously described [ 38 ]. Briefly, the cell-permeable CellROX Deep Red reagent is essentially non-fluorescent while it is in a reduced state, but exhibits a strong fluorogenic signal upon oxidation, providing a reliable measure of ROS in live cells [ 41 ].…”
Section: Methodsmentioning
confidence: 99%